A systematic review and meta‐analysis of preclinical and clinical studies on the efficacy of ginger for the treatment of fatty liver disease. (1st February 2022) - Samadi, Mehnoosh; Moradinazar, Mehdi; Khosravy, Tina; Soleimani, Davood; Jahangiri, Parvin; Kamari, Negin
Abstract: Fatty liver disease (FLD) is the most common chronic liver disease worldwide. The pathogenesis of this disease is closely related to obesity and insulin resistance. Ginger has hypolipidemic and antioxidant effects and acts as an insulin sensitizer. This study aims to evaluate the effect of ginger supplementation on the fatty liver. A comprehensive search of Medline/PubMed, Embase, Scopus, Web of Science/ISI, and Cochrane databases was conducted without time or language restrictions. Eighteen eligible studies were identified, including 17 in‐vivo experiments in quantitative analysis and 3 clinical trials in qualitative analysis. The present study provides comprehensive evidence of the efficacy of ginger to improve the liver levels of cholesterol (−5.60 mg/g), triglycerides (TG, −4.28 mg/g), malondialdehyde (−3.16 nmol/mg), catalase (CAT) (3.35 nmol/mg), superoxide dismutase (SOD, 3.01 U/mg), serum levels of alanine aminotransferase (ALT, −2.85 U/L), aspartate aminotransferase (AST, −0.98 U/L), TG (−4.98 mg/dL), low‐density lipoprotein (LDL, −3.94 mg/dL), total cholesterol (TC, −3.45 mg/dL), high‐density lipoprotein (HDL, 1.27 mg/dL), and fasting blood sugar (FBS, −2.54 mg/dL). Ginger administration may reduce many clinical aspects of FLD by several mechanisms, including insulin‐sensitive effects, stimulating the expression of antioxidant enzymes, reducing the generation of reactive oxygen species (ROS), having antidyslipidemic activities, and reducing hepatic fat content. However, future clinical trials are essential to investigate the clinical application of ginger in this area.